2020
DOI: 10.3390/nu12092523
|View full text |Cite
|
Sign up to set email alerts
|

N-6 Polyunsaturated Fatty Acids and Risk of Cancer: Accumulating Evidence from Prospective Studies

Abstract: Previous studies on the association between polyunsaturated fatty acids (PUFAs) and cancer have focused on n-3 PUFAs. To investigate the association between intake or blood levels of n-6 PUFAs and cancer, we searched the PubMed and Embase databases up to March 2020 and conducted a meta-analysis. A total of 70 articles were identified. High blood levels of n-6 PUFAs were associated with an 8% lower risk of all cancers (relative risk (RR) = 0.92; 95% confidence interval (CI): 0.86–0.98) compared to low blood lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 104 publications
2
27
1
Order By: Relevance
“…This diversity is ultimately reflected in the inter-individual variability of epidemiological studies. It is, therefore, this diversity that is to blame for the inconclusive nature of clinical studies with n-3 LC-PUFAs or dietary supplements rich in n-3 LC-PUFAs [96][97][98][99][100]. Another issue is the level of n-3 LC-PUFAs in animal and clinical studies, which has to be carefully determined to obtain clear anticancer effects [124].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This diversity is ultimately reflected in the inter-individual variability of epidemiological studies. It is, therefore, this diversity that is to blame for the inconclusive nature of clinical studies with n-3 LC-PUFAs or dietary supplements rich in n-3 LC-PUFAs [96][97][98][99][100]. Another issue is the level of n-3 LC-PUFAs in animal and clinical studies, which has to be carefully determined to obtain clear anticancer effects [124].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In addition, all-cause mortality was reduced among 1463 women newly diagnosed with first primary breast cancer with the higher quartile of dietary fatty fish and n-3 LC-PUFAs intake [95]. However, the effect of n-3 LC-PUFAs as dietary supplements before and/or during cancer treatment is somewhat controversial due to the lack of sufficiently robust randomized controlled clinical trials [96][97][98][99][100]. Besides, a very recent study concerning 250 registered n-3 LC-PUFA clinical trials and a screening for pertinence to cancer therapy showed a total of 171 entries [14].…”
Section: Human and Clinical Studies Highlight The Benefit Of N-3 Lc-p...mentioning
confidence: 99%
“…The relationship between circulating PUFA levels and breast cancer has been examined in multiple studies with inconsistent results found. PUFAs are classified as n‐6 and n‐3 depending on the position of the first double bond in the carbon chain 47 . The difference is not limited to the carbon chain as both compete in the body for their uptake through the same pathway, though n‐3 PUFA promote anti‐inflammatory effects 48 and n‐6 PUFA promote proinflammatory reactions 49 .…”
Section: Discussionmentioning
confidence: 99%
“…PGs, especially PGE 2 , play a critical role in immune diseases and inflammation through regulating mast cell activation, T h 1 cell differentiation, T h 17 cell proliferation, and cytokine production [119] , [120] , [121] . Give that inflammation is a key factor in cancer progression, previous studies have investigated the role of the n-6 PUFAs pathway in cancers [ 77 , [122] , [123] , [124] , [125] ]. The COX-2/PGE 2 axis could directly activate EP receptors on cancer cells, resulting in cancer cell proliferation, invasion, EMT, and angiogenesis [ 52 , 54 , 79 , 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%